2017
DOI: 10.1080/00028487.2017.1301994
|View full text |Cite
|
Sign up to set email alerts
|

Matching Watershed and Otolith Chemistry to Establish Natal Origin of an Endangered Desert Lake Sucker

Abstract: Like many native endemic desert freshwater fish species, the June Sucker (Chasmistes liorus) is currently listed as endangered. Implicit within the June Sucker recovery plan, is that spawning habitat restoration must result in natural recruitment. I used otolith microchemistry to establish natal origins of the potamodromous June Sucker endemic to Utah Lake, UT, USA, ultimately in order to evaluate whether tributary habitat restoration results in natural recruitment. My specific objectives included; 1) quantify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 56 publications
3
8
0
Order By: Relevance
“…Consequently, we could not estimate some more complex mark-recapture models as we had originally intended (e.g., by tributary origination, by life stage), as such models are data-hungry and require a long time series. The otolith microchemistry results were extremely useful and interesting, and this approach can offer a powerful tool for reconstructing the life history of a fish, as demonstrated here and elsewhere (e.g., Brenkman et al 2007;Pangle et al 2010;Strohm et al 2017). However, otolith microchemistry will always be limited in applicability for fishes of conservation concern because a fish must be euthanized, though the use of other hard structures (e.g., fin rays) that do not require euthanizing the animal is recently proving promising (e.g., Sellheim et al 2017).…”
supporting
confidence: 57%
See 2 more Smart Citations
“…Consequently, we could not estimate some more complex mark-recapture models as we had originally intended (e.g., by tributary origination, by life stage), as such models are data-hungry and require a long time series. The otolith microchemistry results were extremely useful and interesting, and this approach can offer a powerful tool for reconstructing the life history of a fish, as demonstrated here and elsewhere (e.g., Brenkman et al 2007;Pangle et al 2010;Strohm et al 2017). However, otolith microchemistry will always be limited in applicability for fishes of conservation concern because a fish must be euthanized, though the use of other hard structures (e.g., fin rays) that do not require euthanizing the animal is recently proving promising (e.g., Sellheim et al 2017).…”
supporting
confidence: 57%
“…For the top models (within 2 ΔAICc units) we included the individual covariate total length (TL) to S, R, and R' for the first-year post capture. Survival is often positively related to fish size, and previous work indicates p, R and R' also can vary with fish size (Schaller et al 2014;Budy et al 2017;Clark et al 2018). We only modeled the effect of fish size on the first-year post capture because most fish were not re-measured after initial capture.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The Ba/Ca ratio vs . Sr/Ca ratio in the different tributaries revealed differences that could be used to infer the origin of the water, and, consequently, the movements of fish between them [ 11 , 73 , 74 ]. The differences were particularly marked between the Mekong mainstream and its tributaries [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The differences were particularly marked between the Mekong mainstream and its tributaries [ 11 ]. While Humston et al [ 73 ] and Strohm et al [ 74 ] showed that there was strong linear relationship between Sr/Ca and Ba/Ca in otoliths and water in various tributaries in the USA, the changes in otolith Sr/Ca and Ba/Ca did not reflect the seasonal river flow [ 37 ]. In the present study, the potential of comparing Sr/Ca and Ba/Ca between water and otoliths to determine the origin of fish origin remains questionable.…”
Section: Discussionmentioning
confidence: 99%